Pakan Sapi dari Jerami Padi hasil Amoniasi dan Fermentasi - Zaini, Halim (Jurnal Sains dan Teknologi Reaksi, 2014)
Processing of rice straw with ammoniation process and fermentation through fodder IbM activities intended to change the pattern of majemen cattle ranch pattern towards effective and efficient. Ibm pilot simple form stable, nutritious animal feed and livestock management changes through with implementing health management and livestock fodder. Aspects of the provision of fodder production at any time, especially for feed consumption evenings creating growth and weight gain of cattle faster with feed consumption rate of 0.5 kg s / d 1 kg per cow for local cattle. Management aspects of the farmers more flexibility to adjust working time for various activities such as taking care of livestock, farming, bersawah and other employment matters. Feed production costs an average of IDR 525 / kg straw. The average income of IDR 322. 450, - per month per head.Keywords: straw processing, animal feed, feed consumption, income